SOSIALISASI DAMPAK PENCEMARAN AIR TERHADAP BIOTA AKUATIK DAN STRATEGI PENGENDALIANNYA DI DAERAH ALIRAN SUNGAI CITARUM - Telussa, Riena F.; Rahmatia, Firsty; Nainggolan, Armen (Jurnal Pengabdian Masyarakat Satya Widyakarya, 2023)
The Citarum watershed, the largest in West Java, has experienced severepressure due to exploitation exceeding its carrying capacity. Therefore,managing the Citarum watershed cannot be done sectorally, but must beintegrated and inclusive of all stakeholders, both within and outsidewatershed, to achieve sustainable development. This requires support fromvarious parties, including academics, by promoting outreach activities. Theimplementation methods include observation, introduction, water qualitytesting, outreach sessions, evaluation, consultation and mentoring, as wellmonitoring. Pre-outreach questionnaire results showed that 70% ofparticipants were aware the impacts of waste and pollution on river life. Allparticipants expressed a desire to maintain the cleanliness of Citarum River,yet only 13% had actively taken part in river clean-up activities. Overall, thepre-outreach findings suggest that while awareness exists, communityparticipation in environmental actions especially in keeping the river cleanremains limited and needs to be increased through continuous education andengagement.